Study of Zumba game playing experience, related to previous knowledge of Zumba - Zanardi de Toledo, Patricia (2014)
The focus of this research is to make an analysis of the experiences of Xbox Kinect Zumba game players in correlation to the real Zumba classes. Through the observation of the Zumba game, specifically using the Xbox Kinect motion detection technology, the researcher intends to create a user experience similar to the real classroom experience and/or create a situation pleasant enough to interest the subjects in real Zumba classes or further game playing, despite of their preconceptions about the game/activity. Negative results will be used to pinpoint what is lacking in this situation and environment to achieve the level of comfort and enjoyment required. The researcher intends to show that exergames are ideal replacements for fitness activities for individuals unable to attend fitness facilities and they might increase the interest and self-assurance of the players in taking part of the real life activity. This research intends to deepen the previous work done by Ahonen (2012), focusing on a more specific game and technology and restricting the external influences in game playing. By doing so, the researcher intends to demonstrate that the negative results described by Ahonen were influenced by other factors not related to exergames and that further research deems necessary. This research will also open the doors for a better understanding of exergames and their importance in the fitness and health structure of future generations. It will also allow further longitudinal research to be done on the consequences of extended usage of exergames as fitness and health contributors.